2021
DOI: 10.34172/ijtmgh.2021.17
|View full text |Cite
|
Sign up to set email alerts
|

Transplant Tourism and Organ Trafficking: Current Practices, Controversies and Solutions

Abstract: The controversial subject of transplant tourism has been neglected in the travel medicine literature. According to the Declaration of Istanbul, travel for transplantation can be regarded as transplant tourism if it involves organ trafficking and/or commercialised transplantation activities. While no registry of transplant tourism activities exists, published case series point to significant negative clinical outcomes. Adverse outcomes among donors include postoperative depression and anxiety, deterioration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Since kidney transplantation experienced the most severe decline [ 1 3 ], and since the kidney is the most trafficked donor organ [ 46 ], it can be presumed that the COVID-19 pandemic disrupted organ trafficking. Trafficked and illegally traded organs are transplanted mostly in low-GDP and some mid-GDP countries, but the recipients are often transplantation tourists from high-GDP and mid-GDP countries [ 21 , 47 – 49 ]. Our study indicated that combined kidney transplants declined by 37% and LDK transplants declined by 46% in low-GDP countries.…”
Section: Discussionmentioning
confidence: 99%
“…Since kidney transplantation experienced the most severe decline [ 1 3 ], and since the kidney is the most trafficked donor organ [ 46 ], it can be presumed that the COVID-19 pandemic disrupted organ trafficking. Trafficked and illegally traded organs are transplanted mostly in low-GDP and some mid-GDP countries, but the recipients are often transplantation tourists from high-GDP and mid-GDP countries [ 21 , 47 – 49 ]. Our study indicated that combined kidney transplants declined by 37% and LDK transplants declined by 46% in low-GDP countries.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on West Bengal in India as the region is likely to be involved in transnational kidney trade, particularly with Bangladesh and Nepal, the two countries known as hot spots 8 14 15. Pakistan was selected because it is another known hot spot in the region,16 and also because the kidney trade cases reported in Pakistan tend not to be covered by Bangladeshi newspapers. While Pakistan borders with state or Rajasthan, Punjab, Gujarat, and Jammu and Kashmir in India, we did not include newspapers from those Indian regions as we suspected a low volume of illicit trade between India and Pakistan due to their historically tensed relationships and heightened border security on both sides, as well as thorough background checks of visitors’ visa applications, which make it hard to operate such illicit networks.…”
Section: Data Sourcementioning
confidence: 99%